2022
DOI: 10.1158/1538-7445.am2022-2564
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2564: CDK9 inhibition via KB-0742 is a potential strategy to treat transcriptionally addicted cancers

Abstract: Lineage-specific transcriptional networks drive cellular differentiation and development. Disruption of these specific cell programs can result in cancer and create a subset of tumors that are “transcriptionally addicted.” Sarcomas, for example, are characterized by an oncogenic fusion protein consisting of a FET family RNA-binding protein fused to a transcription factor (TF). The oncogenic fusions result in a restructuring of the transcriptome promoting cancer. In chordoma, TBXT (brachyury)—normally involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Furthermore, recent preclinical data continue to bolster the rationale for targeting CDK9 inhibition in transcriptionally addicted tumors and offer support for trial expansion into other tumors. 69 , 70 …”
Section: Path To the Clinic: Progress And Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent preclinical data continue to bolster the rationale for targeting CDK9 inhibition in transcriptionally addicted tumors and offer support for trial expansion into other tumors. 69 , 70 …”
Section: Path To the Clinic: Progress And Challengesmentioning
confidence: 99%
“…Furthermore, recent preclinical data continue to bolster the rationale for targeting CDK9 inhibition in transcriptionally addicted tumors and offer support for trial expansion into other tumors. 69,70 VIP152 (BAY-1251152), Figure 2 (5), is another highly selective CDK9 inhibitor in Phase I clinical development (NCT02635672), sponsored by Vincerx Pharma, Incorporated. VIP152 is derived from Bayer's atuveciclib to address some of the shortcomings of that compound.…”
Section: Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting orally bioavailable CDK9i is KB-0742, which demonstrated preclinical efficacy in ARdependent castration-resistant prostate cancer [72] and transcriptionally addicted tumors, such as sarcoma and chordoma [73] . It is currently being tested in a Phase I clinical trial that includes DLBCL with MYC translocation and Burkitt lymphoma (NCT04718675).…”
Section: Cyclin-dependent Kinase 7/9 Inhibitorsmentioning
confidence: 99%
“…Since brachyury (like most transcription factors) is a challenging drug target, the authors performed a drug repurposing screen and found that inhibitors of CDK9 or CDK7/12/13 ( 118 ) downregulate TBXT transcription and suppress chordoma cell proliferation. These results have motivated further in vivo testing of transcriptional CDK inhibitors, including KB-0742 ( 119 ), in the Chordoma Foundation’s Drug Screening Program ( 120 ).…”
Section: Unbiased Functional Assays For Target Discovery and Personal...mentioning
confidence: 99%